2018
DOI: 10.1627/jpi.61.171
|View full text |Cite
|
Sign up to set email alerts
|

エタノールからの選択的な1,3-ブタジエン生成におけるMgOの触媒作用とタルク触媒でのZn<sup>2+</sup>の役割

Abstract: 1,3-Butadiene is produced as a by-product during ethylene production from steam crackers. Increasing demand for sustainable chemicals has driven the search for substitute petrochemicals from renewable biomassderived chemical resources. 1,3-Butadiene is an important commodity chemical and an alternative route for its production, from ethanol, was developed about a hundred years ago. In the current climate, the development of a new high-performance catalyst for the bio-based synthesis of 1,3-butadiene is an impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Undoubtedly, ethanol enables the conversion of crotonaldehyde to butadiene, but so does hydrogen, 137 propanol, 34,138 which yields C 3 and C 5 Scheme 6 Mechanisms of crotonaldehyde reduction to crotyl alcohol and its dehydration to butadiene on different catalysts. 99,116,141 96,139,142 Catalysis Science & Technology Mini review byproducts, or even crotyl alcohol itself. 34 Therefore, its role has been the subject of debate.…”
Section: Crotonaldehyde Conversion To Butadienementioning
confidence: 99%
See 1 more Smart Citation
“…Undoubtedly, ethanol enables the conversion of crotonaldehyde to butadiene, but so does hydrogen, 137 propanol, 34,138 which yields C 3 and C 5 Scheme 6 Mechanisms of crotonaldehyde reduction to crotyl alcohol and its dehydration to butadiene on different catalysts. 99,116,141 96,139,142 Catalysis Science & Technology Mini review byproducts, or even crotyl alcohol itself. 34 Therefore, its role has been the subject of debate.…”
Section: Crotonaldehyde Conversion To Butadienementioning
confidence: 99%
“…[143][144][145] Recently, Baba et al reiterated that ethanol is not the sole reducing agent of crotonaldehyde in the ethanol-to-butadiene reaction. This claim stems from the fact that the reaction can proceed on MgO, 96,139,142 but not CaO, despite both being alkaline-earth metal oxides with basic properties. According to the authors, contrary to MgO, CaO cannot perform the heterolytic dissociation of hydrogen.…”
Section: Crotonaldehyde Conversion To Butadienementioning
confidence: 99%
“…[63] Baba's group synthesized Zn and Ge-talc, a 1 : 2 layered magnesium silicate, where one MgO octahedral sheet is sandwiched between two SiO 2 tetrahedral sheets. [69,70] Despite a modest selectivity of 48%, the productivity for Zn-talc was 1.1 g BD g cat À 1 h À 1 , which puts it amongst the most active catalysts. [69] Kinetic studies indicated that Zn promoted the rate of acetaldehyde formation but did not affect the subsequent aldol condensation step.…”
Section: Metal/metal Oxide-promoted Sio 2 à Mgo Catalystsmentioning
confidence: 99%
“…[69,70] Despite a modest selectivity of 48%, the productivity for Zn-talc was 1.1 g BD g cat À 1 h À 1 , which puts it amongst the most active catalysts. [69] Kinetic studies indicated that Zn promoted the rate of acetaldehyde formation but did not affect the subsequent aldol condensation step. In contrast, the Ge-talc had higher BD selectivity, 71%, but a slightly lower activity than Zn-talc.…”
Section: Metal/metal Oxide-promoted Sio 2 à Mgo Catalystsmentioning
confidence: 99%
“…Benefiting from an understanding of the reaction pathway, a more efficient two-step process employing acetaldehyde/ethanol as feedstock was developed ( Figure 2), but there is still a lot of work to do to realize a BD production process with a yield higher than 90%. Although extensive studies have been performed over the past 3 years [36][37][38][39][40][41][42][43][44][45][46][47] (Table 1), as well as several published reviews [17,[48][49][50][51][52][53], the development of efficient processes and robust catalysts still remains a challenge and issues related to carbon efficiency, catalyst cost, toxicity, feedstock tolerance and backend optimization need further investigation [49]. The general reaction mechanism and major by-products of 1,3-butadiene (BD) production from ethanol [19,[23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Catalysts 2018 8 X For Peer Review 3 Of 25mentioning
confidence: 99%